PROFESSIONAL BURNOUT OF MEDICAL WORKERS AND DISTRESS: SITUATIONAL AND PSYCHOLOGICAL FACTORS - Бабанов, Сергей Анатольевич; Лысова, Маргарита Валериановна; Кувшинова, Наталия Юрьевна; Острякова, Наталья Александровна; Бабанов, Андрей Сергеевич (Medicine in Kuzbass, 2025)
The aim of the work is to study the features of professional burnout among internists and surgeons of general and specialized profiles. Research materials and methods. The research was carried out within the framework of a comprehensive topic of the Department of Occupational Diseases and Clinical Pharmacology named after prof. V.V. Kosarev of Samara State Medical University «Problems of polymorbidity, diagnosis, prognosis and prevention of occupational and occupational-related diseases in workers with isolated combined effects of environmental factors and the labor process» (registration number 124053000016-4), registration date 30.05.2024). Patient consent. Each participant in the study gave informed voluntary written consent to participate in the study and publish personal medical information in an impersonal form. The study included: group 1 – gastroenterologists (n = 52 people); group 2 – cardiologists (n = 58 people); group 3 – oncologists of therapeutic (TR) profile (n = 48 people); group 4 – doctors of general surgical (OCR) profile (n = 71 people); group 5 – surgeons of the cardiovascular profile (n = 30 people); group 6 – oncologists surgical (HR) profile (n = 65 people); control group 7 – employees of engineering, technical and economic profiles who are not related to work in medical organizations (healthy) (n = 75 people). Assessment of the level of professional burnout among medical workers was carried out using the MBI methodology developed by K. Maslach, C. Jackson, adapted by N.E. Vodopyanova. The statistical analysis was performed using the R-Studio programming language and environment (R v.4.4.1, RStudio 2024.09.1+394). Descriptive statistics for continuous data were calculated as the average value, 95% confidence intervals; for nonparametric data, the median, 25% and 75% quartiles and interquartile range. Although the data did not correspond to a normal distribution, the groups were larger than 30 observations, which, according to the central limit theorem, allows us to use the mean and 95% confidence intervals to describe the variables. The χ2 criterion was used to compare the percentages. When evaluating differences in nonparametric data groups, the following methods were used the Mann-Whitney criteria for two comparison groups, and the Kraskel-Wallis criteria for more than 2 groups. Results. The professional activity of doctors of the TP and XP profile is associated with the effects of chronic occupational stress,leading to the development of professional burnout. Limitations of the study. The study has regional implications (Samara region) and occupational restrictions (in terms of detailed working conditions in the comparison groups studied). Conclusion. Thus, the data obtained indicate the need to when identifying risk factors for an increase in the level of professional burnout among medical workers who provide medical care in hospitals of therapeutic, general surgical and specialized profiles, to use specialized rehabilitation measures for physicians using relaxation techniques, art therapy, as well as professional adaptation programs; physiotherapy techniques such as electrosleep and reflexotherapy, if possible, sanatorium-resort treatment in sanatoriums, local sanatoriums, etc. with visits to psychotherapy rooms, as well as psychopharmacological medication.